Quality of life (QOL) and well-being research in tourism - Uysal, Muzaffer; Sirgy, M.; Woo, E.; Kim, H. (Pergamon, 2016)
Given the recent proliferation of the research on quality of life and wellbeing in tourism, we review this literature and provide guidance to spur future research. The review focuses on two major constituencies: residents of host communities and tourists. Specifically, the goals of this paper are (1) describe study findings, (2) highlight sampling and data collection methods, and (3) discuss issues of construct measurement. The vast majority of the studies related to these two constituencies show that tourism experiences and activities have a significant effect on both tourists' overall life satisfaction and wellbeing of residents. That is, tourists' experiences and tourism activities tend to contribute to positive affect in a variety of life domains such as family life, social life, leisure life, cultural life, among others. Future research is discussed in relation to these two constituencies.